Impact of the Pandemic on Selected Aspects of Health-Promoting Attitudes in 2020–2021: A Cross-Sectional Study - Kułak-Bejda, Agnieszka; Bejda, Grzegorz; Kułak, Wojciech; Guzowski, Andrzej; Fiłon, Joanna; Łukaszuk, Cecylia; Cybulski, Mateusz; Waszkiewicz, Napoleon; Krajewska-Kułak, Elzbieta (Frontiers in Public Health, 2022)
Introduction In the face of the COVID-19 pandemic, people began to change both their health-promoting and anti-health behaviors. Aim of the Paper To assess the impact of the pandemic on selected health-promoting attitudes. Methods The cross-sectional study was conducted from March 2020 to September 2021. We have used the author's survey questionnaire and the standardized Wellness Behaviors Inventory (WBI). The questionnaires were given to respondents in paper versions to fill it. Results The study group included 600 urban residents aged 32–73. Based on the opinions of the respondents, during the pandemic, the following activities increased the most: hand washing (93.3%), eating sweets and snacks (80%), and surfing the Internet (60%). An increase in drug/legal use was reported by 13.3%, with no indication of a decrease or no change in consumption of the above. The overall WBI index for all subjects before the pandemic was 81.3 ± 20.2 points, and the increase significantly (p < 0.001) during the pandemic was 87.7 ± 16.7 points. In addition, an increase in preferred eating habits was found (from 19.5 ± 6.4 to 21.1 ± 6.9 points; p < 0.001), preferred prophylactic behaviors (from 21.1 ± 6.0 to 22.7 ± 5.2 points; p < 0.001) and level of presented health practices during the pandemic (from 20.3 ± 5.1 to 24.7 ± 2.7 points; p < 0.001), and a decrease significantly (p < 0.001) in the degree of positive mental attitude (from 20.3 ± 5.4 points to 19.3 ± 4.9 points). Conclusions Respondents generally rated their own and their family's health as worse during the pandemic period, and this trend continued when broken down by gender, cohabitant, place of residence, and education. According to the largest group of respondents, the frequency of handwashing, eating sweets and snacks, surfing the Internet, and using drugs/legal highs increased the most during the pandemic. The overall WBI index for all respondents before and during the pandemic was slightly higher during the pandemic period. Monitoring health behavior during a pandemic is essential for prevention and health care institutions. Further studies are needed to assess the long-term impact of the pandemic on pro-and anti-health behavior of people.